MAN-IN-THE-MIDDLE-ATTACK: UNDERSTANDING IN SIMPLE WORDS - Avijit Mallik (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2018)
These days cyber-attack is a serious criminal offense and it is a hot debated issue moreover. A man-in-the-middle-attack is a kind of cyberattack where an unapproved outsider enters into an online correspondence between two users, remains escaped the two parties. The malware that is in the middle-attack often monitors and changes individual/classified information that was just realized by the two users. A man-in-the-middle-attack as a protocol is subjected to an outsider inside the system, which can access, read and change secret information without keeping any tress of manipulation. This issue is intense, and most of the cryptographic systems without having a decent authentication security are threatened to be hacked by the malware named ‘men-in-the-middle-attack’ (MITM/MIM). This paper essentially includes the view of understanding the term of ‘men-in-the-middle-attack’; the current work is mainly emphasized to accumulate related data/information in a single article so that it can be a reference to conduct research further on this topic at college/undergraduate level. This paper likewise audits most cited research and survey articles on ‘man-in-the-middle-attack’ recorded on 'Google Scholar'. The motivation behind this paper is to help the readers for understanding and familiarizing the topic 'man-in-the-middle attack'.